a Brief reflection about capacities, Quality of life and Poverty - Monroy Flores, Verel Elvira (Cooperativismo & Desarrollo, 2015)
In today’s neoclassical-economic world, the space for realization consists of the choice between goods and leisure, where capacities have no place because the only element that makes it possible is the freedom of choice between both (Ortiz-Davison, Ortiz-Mendoza and Cárdenas-Almagro, 2004)1.